Daughters as Blessing or Curse: Islamic Conception and Social Construction - Prof. Dr. Muhammad Sultan Shah; Dr. Ayesha Farooq (jihat-ul-islam, 2020)
The present study intends to develop an understanding regarding the differences between sons and daughters which exist at sociocultural level and the relevant Islamic teachings. It contends that most of the social practices are not a true representation of Islamic teachings. Religion, nevertheless, remains an integral part of almost every social system: it determines normative structures and their functioning. Exploring both the dimensions---social and religious---further enabled us to have a comprehensive understanding of gender conception. These are also helpful in dispelling the long existing misconceptions which have been leading to various objectionable and staunch practices. Most of the available literature and researches have been consulted to develop an in-depth knowledge regarding the female child, whether she is considered as a blessing or a curse. It is found that most of the social practices are in contradiction with the Islamic teachings. Flawed interpretations mislead masses and traditional mindsets are usually resistant to change. Islam emphasized on an unbiased stance for male and female conception, only will of God matters in this regard; however social attitudes are not found the same and deviates from Islamic guidelines in many ways.